Linezolid nanoAntiobiotics and SERS-nanoTags based on polymeric cyclodextrin bimetallic core-shell nanoarchitectures. (1st October 2022) - Hada, Alexandru-Milentie; Potara, Monica; Astilean, Simion; Cordaro, Annalaura; Neri, Giulia; Malanga, Milo; Nostro, Antonia; Mazzaglia, Antonino; Scala, Angela; Piperno, Anna
Abstract: We describe a mild, ecofriendly, and straightforward two-step strategy for making core-shell Au@Ag bimetallic nanoparticles (BMNPs) for antibacterial nanomedicine and SERS imaging. The synthesis exploits the unique properties of the cationic polymeric cyclodextrin (PolyCD) as both reducing and stabilizing agent to obtain, monodispersed and stable Au@Ag BMNPs. PolyCD-driven protocol includes the synthesis of PolyCD-coated Au monometallic nanoparticles (MNPs) as a seed material for the subsequent growing of a silver shell. PolyCD was produced by polymerization of the azido modified βCD monomers with epichlorohydrin and subsequent reduction of azido derivative. The amino groups, as hydrochloride salts (one for CD ring), are pivotal for the formation of BMNPs in mild conditions. Nanoantibiotics and SERS-nanoTag were prepared by complexation of Au@Ag BMNPs with Linezolid (Lz) and 4-mercaptophenyl boronic acid, respectively. Au@Ag@Lz complexes showed a good antibacterial activity against all tested microorganisms including the methicillin resistant Staphylococcus aureus (MRSA). Graphical abstract: Unlabelled Image